INFLUENCE OF FILLER TYPE AND CONTENT ON THE ENGINEERING PROPERTIES OF BITUMEN-STABILIZED GALUNGGUNG SAND - SUKIYO , YUZERWAN
The potential of Galunggung sand for use in road contruction in West Java merits serious consideration. This local material is available in large quantities and has generally satisfactory engineering properties. However, it is deficient in material passing sieve No.200, and both the coarse and fine fractions show high absorption. A previous study indicated that a satisfactory road base material could be obtained by adding silty clay filler in the form of a slurry to Galunggung sand and stabilizing with rapid-curing (RC) cutback bitumen. The objectives of the research described in this thesis were to examine the influence of filler type and content on the engineering properties of Galunggung sand stabilized with cutback bitumen, and to identify the mix combination that best satisfied engineering and cost criteria. Filler materials investigated were Portland cement, crushed rock, silty clay, and silty clay-lime. Filler content investigated were 4 and 10 percent by weight of sand. Slurries were formed using 4, 6 and 8 percent water. The bituminous binder used was an MC cutback and all mixes were allowed to cure for 30 days prior to testing. The investigation indicated that the mix of Galunggung sand with 4 percent silty clay-lime filler, 8 percent water, and 6 percent MC cutback bitumen best satisfied engineering and cost criteria. This mix possesses adequate stability and has relatively low voids. It satisfies flow criteria, has excellent resistance to water, and is relatively inexpensive.